Poitou-Tate duality for arithmetic schemes - Geisser, Thomas; Schmidt, Alexander (Compositio mathematica, 2018)
We give a generalization of Poitou-Tate duality to schemes of finite type over rings of integers of global fields.
Gesehen am 11.02.2019